Drug treatment of psychiatric patients in general practice. Issue 6143 (7th October 1978) - Tyrer, P
Abstract : The prescribing of psychotropic drugs by general practitioners was assessed by analysing the drug treatment of all patients referred from general practice to a psychiatric outpatient clinic over four years. Of the 287 patients, 220 were taking one or more of 56 different psychotropic drugs at referral, diazepam being the most common. Benzodiazepines and barbiturates had been taken for significantly longer than other drugs, and, of a total of 342 drugs, 61 had been prescribed regularly for over a year. Half of the drugs were considered to be incorrectly prescribed on pharmacological grounds, the main errors being unnecessarily prolonged regular treatment, incorrect dosage (particularly common with antidepressants), and polypharmacy with drugs of similar pharmacological action. A basic grounding in the pharmacology of psychotropic drugs might help practitioners to avoid prescribing errors of this kind.